Differences between inexperienced and experienced safety supervisors in identifying construction hazards: Seeking insights for training the inexperienced. (April 2022) - Ouyang, Yewei; Luo, Xiaowei
Highlights: Novices and experienced safety supervisors in hazard identification are compared. Differences in identification results, attention, and scanpaths are found. Experience helps subjects guide their attention to hazardous areas. Experienced safety supervisors are found to observe job sites sequentially. Abstract: The hazard identification ability of frontline safety supervisors is essential to ensure site safety. As experience can benefit the identification performance, this study investigates the gaps between inexperienced and experienced safety supervisors. Thirty-five experienced safety supervisors and 35 novices were invited to identify hazards in 18 virtual construction sites created by 360-degree panoramas. Their identification results, attention allocation, and adopted scanpaths during the identification process were compared. It is found that the experienced significantly spent more fixation time, had more fixations, and gave a larger proportion of attention to hazardous areas. In contrast, the inexperienced had no idea about where might exist hazards in a scenario. They missed hazards due to ignoring the hazardous areas. Besides, it was hard for the inexperienced to recognize hazards requiring in-depth knowledge of safety regulations. They significantly identified fewer hazards except for the relatively obvious hazards: improper use of PPE and struck-by hazards. The scanpaths were more consistent among the experienced. They observed the scene sequentially, without consciously adopting any specific searching patterns from which the novices could learn. Therefore, it is suggested to train the inexperienced to be aware of hazardous areas in workplaces in addition to educating them on safety norms; and provide them chances to practice hazard identification to retain their learned knowledge. The findings reveal the gaps between inexperienced and experienced safety supervisors, providing insights for training the inexperienced and thus helping ensure the job site safety.